PENINGKATAN HASIL BELAJAR BIOLOGI SISWA SMPN 1 MAKASSAR MELALUI PENDEKATAN SAINTIFIK - Athirah Azis, Putri; Bida Purnamasari, Andi (Jurnal Biogenerasi, 2023)
This research is a classroom action research carried out in 2 cycles and through several stages in each cycle used, namely: the planning stage, the implementation of the action, observation and reflection. The purpose of this research is to improve student learning outcomes through a scientific approach in Class VIII SMPN 1 Makassar. The data collection was carried out using the end of the cycle test. The collected data will be analyzed and equipped with a frequency table. Based on the results of research in cycle I, it showed that the learning outcomes of class VIII science students were incomplete because only 9 students who scored >75 or 45% achieved the completeness standard, while in cycle II it showed that there was an increase in students who scored >75. as many as 17 people or 85% where the highest score reached 95 and the lowest score reached 65. In cycle I the average value of student learning outcomes was 65 while in cycle II there was an increase with an average student learning outcome of 82.6. This it can be concluded that through a scientific approach in Class VIII SMPN 1 Makassar can improve learning outcomes.